Entre devires e pertencimentos: a produção da subjetividade entre imigrantes bolivianos em São Paulo - Campos, Geraldo Adriano Godoy de (2009)
This research aims at answering the follow question: how does the production of subjetivity happen in the context of bolivian immigrant labor in the sweatshops in São Paulo? The theme is relevant, considering the conditions of labor exploitation of the bolivian immigrants. The sweatshops in which the exploitation takes places are hired by large brands of the textile industry, through the process of outsourcing. The element of differentiation of this research is present in the theoretical approach itself, since it does not take the concept of identity as an analytical reference. The proposal of this work is to develop the perspective in which the production of subjectivity is not something given a priori, as an immutable essence. Neither is it individual. The subjectivity, composed by heterogeneous elements, is produced in the social sphere. The four plans that are considered as the variables of the research are: labor conditions; legal and political dimension; sociospatial dynamics of the textile production in the city; the functionality of the exploitation of immigrant labor em relation to the selective permeability of the national borders. The methodological approach is qualitative. The techniques used in the research were the interviews and participant-observation, that happen in São Paulo, La Paz (2007 and 2008) and Buenos Aires. The research has also benefit itself from the ethnographic experience from the past years. The results announced suggests that the reproduction of the situation of irregularity, determined by the anachronism of the brazilian legislation, strengthens the construction of an immigrant-illegal-slave-identity that directely affects the production of subjectivity of the bolivian immigrants in São Paulo